Effects of Computer Animations on Students' Geometrical Mathematics Misconceptions in Secondary Schools, Kitui County, Kenya - Simon Warui Mwangi; Bernard Nyingi Githua; Johnson M. Changeiywo (JME (Journal of Mathematics Education), 2021)
Children come across mathematics before they start schooling. From infancy to secondary, they develop mathematical concept formation skills and hold misconceptions. Learning mathematics concepts is spiral in nature, with one level affecting later learning. Poor performance in mathematics is traceable back to Mathematics Misconceptions held by students at an early age. Animations has been used in Symmetry and Matrices with a remarkable reduction of students’ misconceptions. Their use in photoelectric effect in physics signifipppppcantly reduced students’ misconceptions. This study inquired into the effects of computer animations on geometrical misconceptions. The constructivist theory of learning guided the study where prior knowledge in geometry was used to build geometrical concepts from day to-day life experiences. The study employed Solomon-Four Group Design with experimental and control categories having two groups each. The four groups for the study were purposively chosen. 112 boys and 95 girls participated in the research. MAT (Mathematics Achievement Test) adopted from past KCSE (Kenya Certificate of Secondary Education) questions were used to find the misconceptions held by students. The instrument was pilot-tested and resulted in a reliability coefficient of 0.8826 using the KR-20 formula. Pre-testing was done to the control and an experimental group before intervention, and all the four groups sat for a Post-test. ANOVA and t-test were applied in the testing of the hypothesis at a 0.05 level of confidence. With the use of Animation, a reduction of students’ mathematical misconceptions was observed. The performance of boys and girls after exposure to animations were noted to be significantly the same. The findings may help stakeholders in Mathematics Education.